Complexation of calcium and magnesium with glutarimidedioxime: Implications for the extraction of uranium from seawater. (27th July 2015) - Leggett, Christina J.; Rao, Linfeng
Graphical abstract: Amidoxime-based sorbents are promising extractants for uranium in seawater. Complexes of calcium and magnesium with glutarimidedioxime, a ligand that can be formed during sorbent synthesis, were found to be much weaker than uranyl complexes. However, because of their high seawater concentrations, some sorption is expected and should increase with temperature. Abstract: Complexation of calcium and magnesium with glutarimidedioxime, a ligand of importance in the sorption of uranium from seawater by functionalized sorbents, in aqueous solutions was investigated with potentiometry and calorimetry. The stability constants of the complexes and the enthalpies of complexation were determined. Results show that calcium(II) and magnesium(II) form much weaker complexes with glutarimidedioxime than uranium(VI). However, due to the very high concentrations of calcium and magnesium in seawater, small but significant fractions of the sorption sites on the glutarimidedioxime-functionalized sorbent are expected to be occupied by calcium and magnesium. Results also show that the dominant complexation reactions of calcium and magnesium with glutarimidedioxime at seawater pH are endothermic processes, implying that the complexation, as well as the sorption of calcium and magnesium on the glutarimidedioxime-functionalized sorbent, would be enhanced at higher temperatures.